(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
After independence, with the introduction of newPanchayati Raj and community development schemes, constitutional provisionswere made for the upliftment of women. The spread of education, emergence ofpolitical parties, increasing urban contacts, fast means of communication andthe impact of mass-media have brought in a rapid social change in the ruralcommunity which paved the way upto some extent, for the political participationof the rural women. The rural women herself has also started realizinggradually, the importance of participation in the democratic process of thecountry.